Risk Factors Associated With Quality of Life in Patients With Hepatitis B Virus Related Cirrhosis - Zhang, Qi; Zhong, Chunxiu; Cai, Shaohang; Yu, Tao; Xu, Xuwen; Yin, Junhua (Frontiers in Psychology, 2022)
Aim: To evaluate health-related quality of life (HRQoL) of chronic hepatitis B (CHB) and hepatitis B virus (HBV) related cirrhosis patients and analyzed specific differences in all dimensions of HRQoL. Methods: A total of 349 patients met selection criteria were enrolled. The 36-Item Short-Form Health Survey was adopted. Results: Results showed that the physiological HRQoL of the cirrhotic group was significantly lower than that of the non-cirrhotic group (P=0.003), the psychological HRQoL was also lower (P=0.006). HRQoL was significantly negatively correlated with liver stiffness (P=0.001). We further evaluated the risk factors associated with poor HRQoL in HBV-related cirrhosis patients. Results showed that positive HBV DNA viral load (OR=6.296, P=0.041) and HCC family history (OR=36.211, P=0.001) were independent factors associated with HRQoL in HBV-related cirrhosis. For better risk stratification of patients, multivariable analyses were conducted to explore the independent factors that affected specific physiological and psychological HRQoL. In specific physiological HRQoL, results show that marital status (OR=9.971, P=0.034), positive HBV DNA viral load (OR=6.202, P=0.042) and antiviral drugs (OR=0.45, P=0.031) were independent factors associated with physiological HRQoL in cirrhosis patients. In psychological HRQoL, only HCC family history was independent risk factors associated with psychological HRQoL (OR=42.684, P=0.002). Conclusions: We found that the impaired HRQoL dimensions of HBV related cirrhosis patients differ between the various subpopulations. According to our results, risk stratification, medical decision making and personalizing interventions could be made.